A taxonomic revision of Allodynerus Blüthgen (Hymenoptera: Vespidae: Eumeninae) from China - Zhang, Xue; Chen, Bin; Li, Ting-Jing (Zootaxa, 2020)
In this paper, six species of the genus Allodynerus Blüthgen from China are reviewed, including four new species and two known species, namely Allodynerus reduncus Zhang, Chen & Li, sp. nov., Allodynerus bimaculus Zhang, Chen & Li, sp. nov., Allodynerus diqingensis Zhang, Chen & Li, sp. nov., Allodynerus asperipunctarus Zhang, Chen & Li, sp. nov., Allodynerus delphinalis delphinalis (Giraud, 1866) and Allodynerus mandschuricus Blüthgen, 1953. These four new species are described and illustrated in detail, and the two known species are redescribed and illustrated. A key to all known species of Allodynerus worldwide is also provided.